The epidemiology of fracture-related infections in Germany - Nike Walter (Nature Portfolio, 2021)
Abstract The epidemiology of fracture-related infection (FRI) is unknown, which makes it difficult to estimate future demands and evaluate progress in infection prevention. Therefore, we aimed to determine the nationwide burden’s development over the last decade as a function of age group and gender. FRI prevalence as a function of age group and gender was quantified based on annual ICD-10 diagnosis codes from German medical institutions between 2008 through 2018, provided by the Federal Statistical Office of Germany (Destatis). The prevalence of FRI increased by 0.28 from 8.4 cases per 100,000 inhabitants to 10.7 cases per 100,000 inhabitants between 2008 and 2018. The proportion of fractures resulting in FRI increased from 1.05 to 1.23%. Gender distribution was equal. Patients aged 60–69 years and 70–79 years comprised the largest internal proportion with 20.2% and 20.7%, respectively, whereby prevalence increased with age group. A trend towards more diagnoses in older patients was observed with a growth rate of 0.63 for patients older than 90 years. Increasing rates of fracture-related infection especially in older patients indicate an upcoming challenge for stakeholders in health care systems. Newly emerging treatment strategies, prevention methods and interdisciplinary approaches are strongly required.